The Effect of Project Based Learning Model on Creative Thinking Ability and Emotional Intelligence of Grade X Students in Biology - Raicha Oktafiani; Dea Fernandilla; Aulia Novitasari; Aryani Dwi Kesumawardani; Meita Dwi Solviana (WISE Pendidikan Indonesia, 2026)
Creative thinking and emotional intelligence are essential competencies for students facing the demands of twenty-first-century biology learning. Preliminary data at SMA Negeri 12 Bandar Lampung showed that Grade X students' creative thinking ability was still in the less creative category (average 36%), while emotional intelligence was categorized as poor (average 40%). This study examined the effect of the Project Based Learning (PjBL) model on students' creative thinking ability and emotional intelligence in Grade X Biology, particularly on the topic of environmental pollution. A quantitative quasi-experimental method with a pretest-posttest control group design was employed. The population comprised all Grade X students in the even semester of the 2024/2025 academic year (N = 337). Through cluster random sampling, Class X.4 (n = 34) was assigned as the experimental group and Class X.1 (n = 34) as the control group. Data were collected using a validated creative thinking essay test, an emotional intelligence questionnaire, and observation sheets. Instrument reliability was very high for both the creative thinking test (Cronbach's alpha = 0.821) and the emotional intelligence questionnaire (Cronbach's alpha = 0.877). Data were analyzed using descriptive statistics, N-gain, prerequisite testing, and independent samples t-tests through SPSS version 25. The findings showed significant differences between experimental and control groups in creative thinking ability, t(66) = 13.844, p < 0.05, and emotional intelligence, t(66) = 15.440, p < 0.05. The experimental group achieved N-gain scores of 80.91% for creative thinking and 80.51% for emotional intelligence, both in the excellent category, whereas the control group obtained 35.18% and 45.23%, respectively. Visualized indicator-level data further showed that all creative thinking indicators and all emotional intelligence indicators reached very high categories in the experimental group. These results indicate that PjBL is more effective than direct instruction in strengthening creative thinking and emotional intelligence in biology learning. The study contributes empirical evidence for integrating authentic environmental projects into secondary biology instruction.